Maternal and fetal outcomes of SLE in pregnancy: a literature review - Abdul Basit Sangah; Sidra Jabeen; Meklit Zenbabaw Hunde; Sunita Devi; Hassan Mumtaz; Shazia Saleem Shaikh (Journal of Obstetrics and Gynaecology, 2023)
Systemic Lupus Erythematosus (SLE) is an auto-immune disease in which the immune system assaults its tissues. We aimed to analyse the maternal and foetal outcomes during pregnancy in SLE mothers. A literature search was conducted by two investigators to assess SLE's outcomes on maternal and foetal during pregnancies. We searched PubMed/Medline, Embase, and Google scholar to collect evidence from different research studies, draw the conclusion, and report it. In our investigation, we found out that SLE could cause a spectrum of complications during pregnancy, not only for the mother but also for the foetus. It could affect fertility and cause difficult pregnancies for the couple as well which includes certain complications such as: preterm labour and delivery, high blood pressure (preeclampsia), placental insufficiency, miscarriage or stillbirth, whereas in the foetus SLE can cause mortality, preterm birth, and neonatal lupus (a temporary condition in the baby caused by SLE-related antibodies) and structural abnormalities. The literature suggests that SLE could prove fatal for the foetus and induce many complications in the mother. However, this could be avoided if pregnancy is planned right from the start and proper management is provided to the mother during pregnancy and delivery.p